2012
DOI: 10.3389/fnhum.2012.00227
|View full text |Cite
|
Sign up to set email alerts
|

Binocular rivalry produced by temporal frequency differences

Abstract: When the eyes view images that are sufficiently different to prevent binocular fusion, binocular rivalry occurs and the images are seen sequentially in a stochastic alternation. Here we examine whether temporal frequency differences will trigger binocular rivalry by presenting two dynamic random-pixel arrays that are spatially matched but which modulate temporally at two different rates. We found that binocular rivalry between the two temporal frequencies did indeed occur, provided the frequencies were suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 94 publications
(158 reference statements)
0
11
1
Order By: Relevance
“…Last, our findings can be distinguished from those of Alais and Parker (2012), who used spatiotemporally filtered stimuli similar to ours in a binocular-rivalry paradigm. Their competing stimuli were matched for size, contrast, spatial frequency, and orientation content, so that the only difference between them was temporal frequency, which was carefully manipulated.…”
Section: Discussioncontrasting
confidence: 39%
“…Last, our findings can be distinguished from those of Alais and Parker (2012), who used spatiotemporally filtered stimuli similar to ours in a binocular-rivalry paradigm. Their competing stimuli were matched for size, contrast, spatial frequency, and orientation content, so that the only difference between them was temporal frequency, which was carefully manipulated.…”
Section: Discussioncontrasting
confidence: 39%
“…Recent studies show that nonvisual modalities, including audition (Sekuler et al, 1997;Kang and Blake, 2005;Munhall et al, 2009;van Ee et al, 2009;Conrad et al, 2010;Chen et al, 2011), touch Maruya et al, 2007;Holcombe and Seizova-Cajic, 2008;Alais et al, 2010b;Lunghi et al, 2010;Lunghi and Morrone, 2013), and olfaction (Zhou et al, 2010) modulate bistable visual alternations. This study uses temporal frequency rivalry (15 vs 3.75 Hz) to investigate whether auditory or tactile modulations (also 15 or 3.75 Hz) influence rivalry alternations.…”
Section: Introductionmentioning
confidence: 99%
“…Because only one image reaches conscious perception, with the other suppressed from awareness, binocular rivalry is used to investigate the neural correlates of perceptual ambiguity and visual awareness (Logothetis, 1998;Koch, 2007). Rivalry is usually induced by spatial conflict (e.g., orientation, color, or spatial frequency) (Yang et al, 1992;Kovács et al, 1996) or competing visual objects (Tong et al, 1998;Alais and Melcher, 2007;Baker and Graf, 2009). Recently, Alais and Parker (2012) showed that spatially matched random patterns rival vigorously when contrast-modulated at very different rates (e.g., factor of 4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimuli differed only in the temporal frequency in which they modulated in contrast, one at 3.75 Hz and the other at 15 Hz. This type of binocular-rivalry stimulus is known to produce alternations in vision that are comparable to alternations caused by spatially dissimilar stimuli, such as those of a face and a house (Alais and Parker, 2012). During dichoptic viewing of the stimuli, Lunghi et al (2014) presented auditory, tactile, or auditory/tactile stimuli intermittently.…”
mentioning
confidence: 99%